Eucoilinae species (Hymenoptera: Cynipoidea: Figitidae) parasitoids of fruit-infesting dipterous larvae in Brazil: identity, geographical distribution and host associations - Guimarães, Jorge A.; Gallardo, Fabiana E.; Diaz, Norma Beatriz; Zucchi, Roberto A. (Zootaxa, 2003)
The Eucoilinae (Cynipoidea, Figitidae) are koinobiont endoparasitoids of dipterous larvae and along with the Opiinae (Braconidae) they are the most important natural enemies of the frugivorous flies (Tephritidae, Lonchaeidae and Drosophilidae). This paper deals with the identity, geographical distribution and host associations of eucoiline species with these biological characteristics in Brazil and provides a key for their identification. Eight species are studied, namely: Lopheucoila anastrephae (Rohwer, 1919), Odontosema anastrephae Borgmeier, 1935; Tropideucoila weldi Costa Lima, 1940, Aganaspis pelleranoi (Brèthes, 1924), A. nordlanderi Wharton, 1998, Trybliographa infuscata Gallardo, Diaz & Uchôa, 2000, Dicerataspis grenadensis Ashmead, 1896 and Leptopilina boulardi (Barbotin, Carton & Kelner-Pillaut, 1979). New geographic records for Brazil are provided for L. anastrephae, T. weldi, D. grenadensis, O. anastrephae, T. infuscata and L. boulardi. Bionomic observations suggest that A. pelleranoi is the species most frequently associated with tephritid flies and probably, the most useful as a biological control agent. Lopheucoila anastrephae is an important parasitoid of lonchaeids and D. grenadensis and L. boulardi are natural enemies of drosophilids.